1999
DOI: 10.1080/096382899298070
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients ready for discharge from acute care- a multi-dimensional assessment of functions and further care

Abstract: It is important to secure continuing adequate care and rehabilitation for elderly severely impaired stroke patients being discharged early from acute care hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The discharge process for patients with stroke has not been studied to a great extent. Kumlien et al. (1999), in such a study, found that eating difficulties were seldom recorded in discharge summaries and the PRs were found to be poorly structured and missing vital information, implying a potential threat to patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge process for patients with stroke has not been studied to a great extent. Kumlien et al. (1999), in such a study, found that eating difficulties were seldom recorded in discharge summaries and the PRs were found to be poorly structured and missing vital information, implying a potential threat to patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Although informational continuity for persons with chronic illness (e.g., stroke) calls for structured and adequate documentation, few researchers have studied this aspect of continuous stroke care. Information on eating problems has been reported to be scarce among stroke patients discharged to nursing homes (Kumlien et al, 1999). Two Swedish projects investigated documentation in stroke care units and information transfer at discharge (Hassler & Krakau, 2005;Olofsson et al, 2002).…”
Section: The Patient Recordmentioning
confidence: 99%
“…A large proportion of persons who have survived a stroke have decreased autonomy that is caused by speech or language impairment, depression and impaired memory (Kumlien et al, 1999;Tatemichi et al, 1994), stressing the importance of continuity of care and transfer of adequate information among different professionals and care providers. Continuity of care has frequently been addressed and studied from a wide range of perspectives (CEN, 2001;Sparbel & Anderson, 2000).…”
Section: Continuity Of Carementioning
confidence: 99%
“…An earlier study (Kumlien et al, 1999) showed that severely impaired stroke patients discharged to nursing homes had a shorter mean length of stay of 5.6 days on an acute ward before the decision to discharge was taken, in comparison with patients discharged to a rehabilitation ward. Patients discharged to nursing homes were in need of special nursing care, medical care, and various types of rehabilitation.…”
Section: Introductionmentioning
confidence: 98%
“…Patients discharged to nursing homes were in need of special nursing care, medical care, and various types of rehabilitation. They were often cognitively impaired and many suffered from depressive symptoms ( Kumlien et al ., 1999 ).…”
Section: Introductionmentioning
confidence: 99%